2003
DOI: 10.1073/pnas.0230424100
|View full text |Cite
|
Sign up to set email alerts
|

Gatm, a creatine synthesis enzyme, is imprinted in mouse placenta

Abstract: To increase our understanding of imprinting and epigenetic gene regulation, we undertook a search for new imprinted genes. We identified Gatm, a gene that encodes L-arginine:glycine amidinotransferase, which catalyzes the rate-limiting step in the synthesis of creatine. In mouse, Gatm is expressed during development and is imprinted in the placenta and yolk sac, but not in embryonic tissues. The Gatm gene maps to mouse chromosome 2 in a region not previously shown to contain imprinted genes. To determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 50 publications
4
43
0
Order By: Relevance
“…It was expressed in the placenta and the yolk sac of mouse embryos. However, no expression was found in the embryonic tissues of mouse (Sandell et al, 2003). Similarly, human agat was also expressed in the placentas (Monk et al, 2006).…”
mentioning
confidence: 90%
“…It was expressed in the placenta and the yolk sac of mouse embryos. However, no expression was found in the embryonic tissues of mouse (Sandell et al, 2003). Similarly, human agat was also expressed in the placentas (Monk et al, 2006).…”
mentioning
confidence: 90%
“…On the other hand, AGAT, GAMT and SLC6A8 are also well expressed during vertebrate embryogenesis, including in the brain (Schloss et al 1994;Sandell et al 2003;Schmidt et al 2004;Braissant et al 2005;Wang et al 2007;Ireland et al 2009). We have shown that AGAT and GAMT are expressed in the whole developing CNS parenchyma (Braissant et al 2005).…”
Section: Adult Versus Developmental Cnsmentioning
confidence: 99%
“…We have analyzed the human imprinted expression of genes on other chromosomes that exhibit placental-specific imprinting in the mouse, glycine amidinotransferase (Gatm) (mChr2) and decorin (Dcn) (mChr10) (26,27). In the mouse, both are isolated imprinted genes without associated DMRs.…”
Section: Allelic Expression and Methylation Within The Kcnq1 Domainmentioning
confidence: 99%